Over 30 Years of Misidentification: A New Nothospecies Lycoris × jinzheniae (Amaryllidaceae) in Eastern China, Based on Molecular, Morphological, and Karyotypic Evidence - Si-Yu Zhang; Ying-Feng Hu; Hao-Tian Wang; Peng-Chong Zhang; Jian-Wen Shao (Plants, 2022)
Based on the complete chloroplast genome, morphology, and karyotype evidence, we identified a new nothospecies, Lycoris × jinzheniae S.Y. Zhang, P.C. Zhang & J.W. Shao, in eastern China. This new nothospecies has been inappropriately named Lycoris × albiflora in the previous literature for more than 30 years. However, the new nothospecies resulted from the hybridization of L. sprengeri and L. chinensis and had the following characteristics: the karyotype was 2n = 19 = 3V + 16I, the leaves emerged in the spring, the ratio of filament to corolla length was approximately 1.2, tepals were slightly undulated and curved, and it was distributed throughout eastern China. These characteristics are quite different from those of L. × albiflora; thus, in this study, we named it and provided a detailed morphological description and diagnosis.